Effects of novel supramaximal interval training versus continuous training on performance in preconditioned collegiate, national, and international class rowers - Richer, S. D.; Nolte, V. W.; Bechard, D. J.; Belfry, G. R. (The Journal of Strength and Conditioning Research, 2016)
This investigation compared supramaximal oxygen uptake interval training with continuous training in collegiate, national, and international class rowers. It was hypothesized that 6 supramaximal intensity sessions over 11 days would increase power on selected power measures. After 8 weeks of training for a new season, 10 heavyweight and 6 lightweight rowers were randomized into 2 groups. A ramp test to limit of tolerance to determine peak aerobic power (6 females: 25 W/min; 10 males: 30 W/min) and an all-out 3-minute test to determine peak power, 60-second power, critical power, and work above critical power (W') were performed before and after training. A supramaximal training session consisted of 10 cycles of 10-second work (140% peak aerobic power):5-second recovery followed by 8 minutes of active recovery, and repeated 6 times. The continuous group performed predominantly moderate intensity (below lactate threshold) training. All training was performed on rowing ergometers. Critical power increased pre-to-post supramaximal (d7%) and continuous training (d9%), respectively (336 ± 59W to 360 ± 59W; 290 ± 73W to 316 ± 74W; p = 0.05), whereas the mean power output from all performance measures increased only after supramaximal training (d7%) (464 ± 158W to 496 ± 184W; p = 0.05). Testing also revealed decreased W' (d21%) and 60-second power (d4%) pre-to-post continuous training only (p = 0.05). No differences (p > 0.05) in peak aerobic power or peak power were observed pre-to-post training in either group. In conclusion, after an 8-week preconditioning period, supramaximal interval training preserved anaerobic capacity compared with predominantly continuous training and elicited similar increases in critical power in rowers.